Community Homestay Management Assistance - Nurfadilah, Nurfadilah; Syah, Arzal; Suci, Suci; Ginanjar, Muhammad; Hamida, Hamida (Advances in Community Services Research, 2024)
Purpose: This study aims to enhance homestay management involving the local community. The goal is to improve service quality and management to support the local economic sustainability of the Rinding Allo Village community in Rongkong District. Research Design and Methodology: This research utilizes a methodological approach that combines observation, interviews, and focus group discussions to identify potentials and challenges in homestay management. Findings and Discussion: The results indicate a significant improvement in homestay management and service skills due to the training and mentoring provided. This has led to the establishment of new standards in the services and facilities offered by homestays. The research highlights the importance of continuous training and structured management practices to achieve these improvements. Implications: This study's implications are highly relevant for the development of other tourist villages in Indonesia, where similar approaches can be applied to support sustainable economic growth through local tourism. Emphasizing the enhancement of local human resource capacity and tourism service quality, this study provides a model that can be replicated in various rural settings. The findings suggest a pathway to achieving long-term sustainability and economic benefits through rural tourism initiatives by fostering local community involvement and improving management practices.